Correlation of endothelial cell proliferation with vascular endothelial growth factor in endometrium of women with menorrhagia - Mehra, Kiran B.; Gangane, Nitin M.; Joshi, Deepti R. (International Journal of Research in Medical Sciences, 2017)
Background: Approximately 30% of women of reproductive age experience excessive blood loss during menstruation. In 50% of cases, menorrhagia has no underlying pathology. However, until recently, the only permanent cure for menorrhagia was hysterectomy. In this study we aim to determine the correlation of vascular endothelial growth factor (VEGF) expression with markers of endometrial endothelial cell proliferation like proliferating cell nuclear antigen (PCNA) and Cluster Determination (CD34). Methods: A total of 100 patients with history of menorrhagia were selected for study. Double Immunohistochemistry was performed on these endometrial biopsy sections. Proliferating endothelial cells were identified by an immunohistochemical double staining technique with PCNA and CD34. VEGF expression was also seen in endometrial biopsy. Results: In general, expression of both VEGF and PCNA was more in functional layer than basal layer in both menorrhagic patients as well as non menorrhagic patients. When glandular cytoplasmic VEGF expression was compared with PCNA the association was statistically significant whereas completely opposite findings was seen with glandular luminal surface VEGF positivity but the association was statistically significant. In secretory phase (p-value<0.001) there was highly statistically significant association in PCNA grading with glandular luminal surface VEGF positivity whereas when we correlated PCNA with cytoplasmic glandular VEGF in secretory phase it was statistically significant (p-value<0.001). Conclusions: The endothelial proliferation was significantly higher in menorrhagia patients during late secretory phase of cycle than controls. We were able to demonstrate increased endothelial proliferation in patients in the premenstrual part of cycle.